Single molecule measurements of microRNAs in the serum of patients with pulmonary tuberculosis - Wu, Zhuhua; Tan, Qiuchan; Jia, Xiaojuan; Wu, Huizhong; Liang, Jing; Wen, Wenpei; Wang, Xuezhi; Zhang, Chenchen; Zhao, Yuchuan; Chen, Yuhui; Luo, Tingrong; Liu, Wenjun; et al. (Frontiers in Immunology, 2024)
Background: microRNAs (miRNAs) were recognized as a promising source of diagnostic biomarker. Herein, we aim to evaluate the performance of an ultrasensitive method for detecting serum miRNAs using single molecule arrays (Simoa).In this study, candidate miRNAs were trained and tested by RT-qPCR in a cohort of PTB patients. Besides that, ultrasensitive serum miRNA detection were developed using the Single Molecule Array (Simoa) platform. In this ultra-sensitive sandwich assay, two target-specific LNA-modified oligonucleotide probes can be simply designed to be complementary to the half-sequence of the target miRNA respectively. We characterized its analytical performance and measured miRNAs in the serum of patients with pulmonary tuberculosis and healthy individuals.We identified an five signature including three upregulated (miR-101, miR-196b, miR-29a) and two downregulated (miR-320b, miR-99b) miRNAs for distinguishing PTB patients from HCs, and validated in our 104 PTB patients. On the basis of Simoa technology, we developed a novel, fully automated digital analyzer, which can be used to directly detect miRNAs in serum samples without pre-amplification. We successfully detected miRNAs at femtomolar concentrations (with limits of detection [LODs] rangng from 0.449 to 1.889 fM). Simoa-determined serum miR-29a and miR-99b concentrations in patients with PTB ((median 6.06 fM [range 0.00-75.22]), (median 2.53 fM [range 0.00-24.95]), respectively) were significantly higher than those in HCs ((median 2.42 fM [range 0.00-28.64]) (P < 0.05), (median 0.54 fM [range 0.00-9.12] (P < 0.0001), respectively). Serum levels of miR-320b were significantly reduced in patients with PTB (median 2.11 fM [range 0.00-39.30]) compared with those in the HCs (median 4.76 fM [range 0.00-25.10]) (P < 0.001). A combination of three miRNAs (miR-29a, miR-99b, and miR-320b) exhibited a good capacity to distinguish PTB from HCs, with an area under the curve (AUC) of 0.818 (sensitivity: 83.9%; specificity: 79.7%).This study benchmarks the role of Simoa as a promising tool for monitoring miRNAs in serum and offers considerable potential as a non-invasive platform for the early diagnosis of PTB.